Kelayakan Hair Tonic Jahe Pada Jenis Rambut Rontok - Sinaga, Rossa; Putri, Arima; Yevawelita , Zera Rahmiati (Jurnal Tata Rias, 2024)
This study aims to analyze a ginger-based hair tonic product in preventing hair loss. The hair tonic is made from natural ginger, which is known for its potential to improve hair health and prevent hair loss. The study was conducted using a quantitative experimental method involving 12 female participants with hair loss issues. The participants were divided into a treatment group that used a ginger hair tonic and a control group that used other commercial products proven effective in preventing hair loss. The results showed that the use of ginger hair tonic significantly reduced the hair loss rate in the treatment group participants. During the 2-week usage period, the participants reported increased hair thickness, a significant reduction in hair loss, and improved shine and softness of their hair. Hedonic testing was also conducted to evaluate the users' preference for the ginger hair tonic. The results of the hedonic test showed that the majority of respondents liked the aroma and absorption power of the ginger hair tonic, but there were some uncertainties regarding the texture and color of the product. Nevertheless, the ginger hair tonic still showed potential as a preferred product among the majority of respondents. In further development, it is important to consider the feedback from the hedonic test to improve the formulation of the ginger hair tonic. This study provides promising preliminary evidence on the feasibility of using ginger hair tonic in naturally preventing hair loss.